2021
DOI: 10.1002/aenm.202003685
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Ions Electrolyte Enabled High Performance Voltage Tailorable Room‐Temperature Ca‐Metal Batteries

Abstract: Calcium metal batteries, as one of the promising alternatives beyond Li‐metal technology, is held back by the lack of suitable cathodes of considerable energy storage capability, and Ca anodes of long‐term stability and lower polarization potentials for Ca‐plating/stripping. Here, by recycling cellulose waste paper, feasible cathodes for Ca‐metal batteries of good high‐voltage and wide‐window‐voltage adaptability (0.005–4.9 V versus Ca/Ca2+), and impressive energy density (≈517.5 Wh kg−1 at 0.1 A g−1) are deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Similarly, Li/Ca hybrid SEIs, comprising of nanocrystals of LiH, Li 3 PO 4 , and a small amount of CaF 2 , were also verified to be applicable for lowering overpotentials and enhancing cycling stability, as well as tailoring deposition layer from dendritic crystal growth in Ca(BF 4 ) 2 electroyte to uniform planar growth in Ca(BF 4 ) 2 ‐LiPF 6 hybrid electrolyte, as shown in Figure . [ 61 ] These results demonstrate that plating/stripping reversibility of Ca‐metal and interface charge transfer kinetics of electrode–electrolyte can be properly tailored through rational engineering of electrolyte and interphase.…”
Section: Engineering Of Electrolyte and Interphasementioning
confidence: 93%
See 4 more Smart Citations
“…Similarly, Li/Ca hybrid SEIs, comprising of nanocrystals of LiH, Li 3 PO 4 , and a small amount of CaF 2 , were also verified to be applicable for lowering overpotentials and enhancing cycling stability, as well as tailoring deposition layer from dendritic crystal growth in Ca(BF 4 ) 2 electroyte to uniform planar growth in Ca(BF 4 ) 2 ‐LiPF 6 hybrid electrolyte, as shown in Figure . [ 61 ] These results demonstrate that plating/stripping reversibility of Ca‐metal and interface charge transfer kinetics of electrode–electrolyte can be properly tailored through rational engineering of electrolyte and interphase.…”
Section: Engineering Of Electrolyte and Interphasementioning
confidence: 93%
“…[76] Research of solvation properties of Ca 2þ also showed coordination number, distances, and species in solvation shell were highly relevant with concentrations. [77] Hence, through proper electrolyte and [45] Ca(BF 4 ) 2 0.45 M in EC/PC SS CaF 2 , hydroxide, carbonate 100 C, 0.05 mA cm À2 and 0.017 mAh cm À2 for 92 h, 0.05 V overpotential, negligible potential shift, 3.5 V anodic stability for Al [66] Ca(BF 4 ) 2 1 M in EC/PC Cu Unknown phase >1 V overpotential, observed Ca deposits, nearly inactive [71] Ca(BF 4 ) 2 1 M in EMI þ TFS Àa) Cu CaF 2 , CaS >1 V overpotential, observed Ca deposits, nearly inactive [72] Ca(BF 4 ) 2 1 M EC/DEC Ca CaF 2 >1 V overpotential, nearly inactive [61] Ca(PF 6 ) 2 1 M EC/DEC Ca CaF 2 >1 V overpotential, nearly inactive [59] Ca(ClO 4 ) 2 0.5 M in BL b) , or PC, or ACN Ca CaCl 2 , CaCO 3 , Ca(OH) 2 , >1 V overpotential at 5 mV s À1 , nearly inactive [67] Ca(ClO 4 ) 2 0.3 M in EC/PC SS Ca(OH) 2 75-100 C, >1 V overpotential at 0.5 mV s À1 , 0.004 mA stripping current, nearly inactive [66] Ca(TFSI) 2 0.1 M and 0.45 M in EC/PC Ca CaCO 3 25-100 C, charge transfer resistance >10 6 Ohm, inactive [83] Ca(TFS) 2 0.1 M in DMF c) SS -Corrosive [45] Ca(TFS) 2 0.05 M in DEME þ TFSA À , 0.1-0.3 M in TMP Ca -60 C, negligible capacity, inactive [55] Ca(BH 4 ) 2 1.5 M in THF Au CaH 2 1 mA cm À2 and 1 mAh cm À2 for 100 h, 0.1 V overpotential, negligible potential shift. <3 V anodic stability for Pt, 94-96% CE at 1 mA cm À2 [15] Ca[B(hfip) 4 ] 2 0.25 M in DME Pt, Ca CaF 2 0.1-0.5 mA cm À2 and 0.05-0.25 mAh cm À2 for 250 h, <0.06->0.5 V overpotential, little potential shift, 4.8 V anodic stability for Al, 80% CE at 80 mV s À1 [16] Ca[B(hfip) 4 ] 2 0.5 M in DME Au CaF 2 0.5 mA cm À2 and 1 mAh cm À2 for 72 h, 0.2 V overpotential, little potential shift, 4.1 V anodic stability for Al, 92% CE at 25 mV s À1 [17] Ca[B(hfip) 4 ] 2 0.25 M in DGM GC, Cu, Al, Pt CaF 2 1-8 mA cm À2 for 300 h, <0.1->0.5 V overpotential, 61-85% CE at 100 mV s À1 [53] a)…”
Section: Engineering Of Electrolyte and Interphasementioning
confidence: 98%
See 3 more Smart Citations